Electrochemical allylations in a deep eutectic solvent - Taylor, Sophia; Handy, Scott T. (Beilstein Journal of Organic Chemistry, 2024)
Electrosynthesis is a technique that is attracting increased attention and has many appealing features, particularly its potential greenness. At the same time, electrosynthesis requires a solvent and a supporting electrolyte in order for current to pass through the reaction. These are effectively consumable reagents unless a convenient means of recycling can be developed. As part of our interest in unusual solvents and electrochemistry, we explored the application of simple, inexpensive, and recyclable deep eutectic solvents to the allylation of carbonyls. While several sets of conditions were developed, the goal of avoiding stoichiometric amounts of metal has proven elusive. Still, a deep eutectic solvent can be used to plate out and thus recover the metal used, offering an interesting new option for electrochemical allylations.
Keywords: allylation; electrosynthesis; eutectic solvent; recycling; tin